Integrating Banking Fundamental Factors with Financial Technologies in Increasing Banking Performance - Rakhmat, Adrianna Syariefur; Mohammad Hatta Fahamsyah; Preatmi Nurastuti; Muhammad Hamdan Ainulyaqin (Ilomata International Journal of Management, 2024)
The existence of innovation involving the adoption of technology in banking has boosted financial performance, where banks get sizable benefits. The use of technology in financial services or known as fintech not only produces new products and models in financial services, but has created solutions. This research is a quantitative research with secondary data sourced from the Financial Services Authority and Bank Indonesia from April 2020 to April 2023. The object of this research is all banks in Indonesia whose data has been aggregated. The variables used in the research are fintech as the independent variable, and banking profitability as the dependent variable, then adding banking fundamentals as a control variable . Meanwhile the analysis technique to be used is Ordinary Least Square (OLS). Fintech can optimize its role in supervising customers which can have an impact on minimizing non-performing loans so that it can increase profitability. The next thing is that even though costs increase it can actually increase profitability. The role of fintech in this case is that although the adoption of fintech will increase costs, profitability will also increase. The level of financing represented by LDR can be maximized in percentage in order to increase profitability.